What's the point of being green? - Bailey, Jacqui; McCafferty, Jan. (New York : Barron's Educational Series, 2010)
Discusses a variety of environmental issues, with suggestions for things that organizations, governments, and individuals can do to help, covering topics such as energy efficiency, climate change, recycling, and population growth.
So, what's the problem? -- What are we doing to the climate? -- Why do we burn fossil fuels? -- What's the alternative? -- But what about cars? -- Why are trees important? -- How did it get so bad? -- Why do some people go hungry? -- Boy, have we messed up! -- What a load of garbage! -- Going, going, gone! -- Isn't anyone doing anything?
Originally published: London : Franklin Watts, 2010.
Includes bibliographical references (p. 90-91) and index.
Keywords: Green movement -- Juvenile literature; Sustainable living -- Juvenile literature